Social stereotypes about ageing among university students of Sports Science. A pilot study - Jose Mª Cancela Carral; Angel Casal-Moldes; Elena Vila-Suarez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Ageing is a natural process in every living being. This process can be seen from different perspectives, and these perceptions can influence how older adults are treated in society. Research conducted among university students on their perception and stereotypes of old age is scarce and very recent.